Perovskite light-emitting devices

By using counterion conjugated polymers on the hole transport layer of the perovskite luminescent device and forming a passivation effect, the problem of reducing luminescent efficiency caused by interface defects in the perovskite luminescent device is solved, and higher luminescent efficiency and longer device life are achieved.

CN113169275BActive Publication Date: 2025-03-14LG DISPLAY CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980079130.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-30
Filing Date
2019-11-20
Publication Date
2025-03-14
Estimated Expiration
2039-11-20

AI Technical Summary

Technical Problem

The presence of interface defects in perovskite luminescent devices leads to a reduction in luminescence efficiency, and conventional hole transport layer materials such as PEDOT:PSS will affect the lifetime, performance and stability of the device.

Method used

When growing a perovskite luminescent layer on the hole transport layer, a conjugated polymer with specific counter ions is used instead of PEDOT:PSS, and a passivation effect is formed between the hole transport layer and the perovskite luminescent layer to avoid a separate passivation layer.

Benefits of technology

It effectively prevents defects in the perovskite luminescent layer, improves luminescence efficiency, extends the life of the device, and improves performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113169275B_ABST
    Figure CN113169275B_ABST
Patent Text Reader

Abstract

The present invention relates to a perovskite light-emitting diode. According to the present invention, by replacing PEDOT:PSS contained in a conventional hole transport layer with an anionic conjugated polymer having an ammonium-based counter ion, the degradation of the light-emitting device characteristics caused by PEDOT:PSS can be prevented, and by passivating the defects of the perovskite light-emitting layer with a hole transport layer containing a conjugated polymer and improving crystal growth, the light-emitting characteristics can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a perovskite light-emitting device. Background Art

[0002] Currently, the display industry is shifting from inorganic light-emitting devices to organic light-emitting devices. Due to the flexible characteristics, relatively simple structure and preparation process, and light weight of organic light-emitting devices, they are attracting attention as the next generation of flexible electronic devices. In addition, due to the high color purity of inorganic quantum dot materials, they are attracting attention second to organic light-emitting devices.

[0003] However, even though organic light-emitting devices have high efficiency, their emission spectra have a wide full width at half maximum (FWHM), resulting in poor color purity. Inorganic quantum dots, whose emission color is controlled by the size of the quantum dots, have good color purity. However, it is difficult to control the size of the quantum dots during the synthesis process.

[0004] In addition, due to the high preparation costs of organic light-emitting devices and inorganic quantum dot materials, they are limited in the production of low-priced products. Therefore, the interest in perovskite light-emitting devices with high color purity, simple preparation process and lower preparation cost is increasing.

[0005] In particular, metal halide perovskite materials are inexpensive. Their synthesis methods are very simple. Metal halide perovskite materials can be dissolved and processed. In addition, metal halide perovskite materials have photoluminescence and electric field electroluminescence properties and can be applied to light-emitting devices.

[0006] However, although metal halide perovskites may have such advantages for light-emitting devices, metal halide perovskites may have limitations in applying them to light-emitting devices.

[0007] First, due to various defects at or within the perovskite interface, the luminescence efficiency is degraded.

[0008] For example, point defects and linear grain boundaries act as traps, thereby causing electrons and holes to recombine non-radiatively in a thermal form. Therefore, in light-emitting devices and solar cells, their efficiency may be deteriorated. In other words, since the energy level of these defects exists between the energy levels of the conduction band and the valence band, electrons or holes are trapped at the energy level of the defect, thereby limiting the transfer of charges, thus causing undesirable non-radiative recombination.

[0009] In order to reduce such defects, a passivation layer can be formed before forming the perovskite light-emitting layer. However, conventional materials used to form the passivation layer are generally not conductive, which is disadvantageous in terms of hole or charge transport.

[0010] Secondly, the perovskite light-emitting layer is usually arranged on top of the hole transport layer. PEDOT:PSS used as the hole transport layer material exhibits strong acidity, thus adversely affecting the lifetime, performance and stability of the light-emitting device. In addition, reported research results have shown that fluorescence quenching of excitons occurs severely at the interface between PEDOT:PSS and the active layer. Summary of the invention

[0011] Technical Purpose

[0012] An object of the present disclosure is to provide a perovskite light-emitting device, in which defects in the perovskite light-emitting layer can be prevented when the perovskite light-emitting layer is grown on the hole transport layer without introducing a separate passivation layer between the hole transport layer and the perovskite light-emitting layer.

[0013] Furthermore, an object of the present disclosure is to provide a perovskite light-emitting device in which PEDOT:PSS contained in a conventional hole transport layer is replaced with a conjugated polymer having specific counter ions, thereby preventing a reduction in light-emitting characteristics caused by PEDOT:PSS.

[0014] The purpose of the present disclosure is not limited to the above-mentioned purpose. Other purposes and advantages of the present disclosure not mentioned above can be understood from the following description and can be more clearly understood from the embodiments of the present disclosure. In addition, it is easy to understand that the purposes and advantages of the present disclosure can be achieved by features and combinations thereof as disclosed herein.

[0015] Technical Solution

[0016] The perovskite light-emitting device according to the present disclosure includes a first electrode; a hole transport layer disposed on the first electrode; a perovskite light-emitting layer disposed on the hole transport layer; an electron transport layer disposed on the perovskite light-emitting layer; and a second electrode disposed on the electron transport layer.

[0017] Wherein, the hole transport layer comprises a compound represented by the following Chemical Formula 1 or the following Chemical Formula 2;

[0018] [Chemical formula 1]

[0019] -Ar1-Ar2-

[0020] [Chemical formula 2]

[0021]

[0022] Wherein Ar1 is represented by the following chemical formula 3:

[0023] [Chemical formula 3]

[0024]

[0025] wherein each of R1 and R2 is independently selected from -C n H 2n -X - Y + (n is an integer from 1 to 20) and -Ar3-(OC n H 2n -X - Y + ) l (n is an integer from 1 to 20, l is an integer from 1 to 3),

[0026] wherein Ar3 is phenyl, pyrrolyl, furyl, thienyl or selenophenyl, wherein X - SO3 - 、CO2 - or PO3 2- , and Y + Yes H + , Li + 、Na + , K + , Rb + , Cs + NH4 + or NR3R4R5R6 + , wherein each of R3 to R6 is independently selected from an alkyl group having 1 to 20 carbon atoms, wherein Ar2 is a substituted or unsubstituted aryl group, and wherein m is an integer from 2 to 1,000,000.

[0027] Technical Effects

[0028] According to the present disclosure, PEDOT:PSS contained in a conventional hole transport layer is replaced with a conductive conjugated polymer having an ionic functional group, thereby preventing degradation of the lifespan, performance, and stability of a light-emitting device caused by acidic PEDOT:PSS while maintaining the characteristics of the hole transport layer.

[0029] In addition, the conjugated polymer contained in the hole transport layer has a specific counter ion, thereby imparting an interface passivation effect between the hole transport layer and the perovskite light-emitting layer. Therefore, when the perovskite light-emitting layer is grown on the hole transport layer, defects in the perovskite light-emitting layer can be suppressed. Therefore, it is not necessary to form a separate passivation layer on the hole transport layer to prevent defects in the perovskite light-emitting layer.

[0030] In addition to the above-described effects, specific effects of the present disclosure will be described while describing specific details of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 A cross-sectional view of a perovskite light-emitting device according to an embodiment of the present disclosure is schematically shown.

[0032] Figure 2 An energy diagram of a perovskite light-emitting device using PEDOT:PSS and a compound represented by Chemical Formula 1 or Chemical Formula 2 (FPS-K, FPS-TMA, MPS-TMA) is shown.

[0033] Figure 3 The UPS measurement results of the HOMO energy level of the hole transport layer of the perovskite light-emitting device prepared according to Comparative Example 1 are shown.

[0034] Figures 4 to 6 The UPS measurement results of the HOMO energy level of the hole transport layer of the perovskite light-emitting devices prepared according to Examples 1 to 3 are shown.

[0035] Figure 7 The measurement results of the contact angle of water on the surface of the hole transport layer of the perovskite light-emitting device prepared according to Comparative Example 1 are shown.

[0036] Figures 8 to 10 The measurement results of the contact angle of water on the surface of the hole transport layer of the perovskite light-emitting devices prepared according to Examples 1 to 3 are shown.

[0037] Fig.11 The measurement results of PL lifetime of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown.

[0038] Fig.12 The measurement results of the current density of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown.

[0039] Fig.13 The measurement results of the luminance of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown.

[0040] Fig.14 The measurement results of the luminous efficiency of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown.

[0041] Fig.15 The measurement results of the external quantum efficiency of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown.

[0042] Fig.16 The measurement results of changes in external quantum efficiency of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 before and after aging are shown.

[0043] Fig.17The XPS analysis results of the perovskite light-emitting layers of the perovskite light-emitting devices prepared according to Example 1, Example 2 and Comparative Example 1 are shown, except that a 10 nm thick perovskite light-emitting layer is formed.

[0044] Fig.18 The XRD analysis results of the perovskite light-emitting layers of the perovskite light-emitting devices prepared according to Example 1, Example 2 and Comparative Example 1 are shown, except that a 10 nm thick perovskite light-emitting layer is formed.

[0045] Fig.19 The XPS analysis results of the 150 nm thick perovskite light-emitting layer of the perovskite light-emitting device prepared in the same manner as in Example 1, Example 2 and Comparative Example 1 are shown.

[0046] Fig. 20 The XRD analysis results of the 150 nm thick perovskite light-emitting layer of the perovskite light-emitting device prepared in the same manner as in Example 1, Example 2 and Comparative Example 1 are shown.

[0047] Fig.21 The measurement results of changes in external quantum efficiency based on the electrical stress (current density) applied to the perovskite light-emitting devices prepared according to Example 1, Example 2, and Comparative Example 1, respectively, are shown.

[0048] Fig. 22 The measurement results of changes in external quantum efficiency before and after applying electrical stress to the perovskite light-emitting devices prepared according to Example 1, Example 2 and Comparative Example 1, respectively, are shown. DETAILED DESCRIPTION

[0049] The objects, features and advantages described above will be described in detail below with reference to the accompanying drawings. Therefore, a person with ordinary knowledge in the technical field to which the present disclosure belongs can easily implement the technical ideas of the present disclosure. When describing the present disclosure, when it is determined that the detailed description of known parts related to the present disclosure may unnecessarily obscure the main points of the present disclosure, the detailed description thereof is omitted. Hereinafter, the preferred embodiments of the present disclosure will be described in detail with reference to the accompanying drawings. The same reference numerals in the accompanying drawings are used to represent the same or similar parts.

[0050] In addition, it will also be understood that when a first element or layer is referred to as being “on (or under)” a second element or layer, the first element may be directly disposed on or under the second element, or may be indirectly disposed on or under the second element with a third element or layer disposed between the first element or layer and the second element or layer.

[0051] It will be understood that when an element or layer is referred to as being “connected to” or “coupled to” another element or layer, it can be directly on, directly connected to, or directly coupled to the other element or layer, or one or more intervening elements or layers may be present. Additionally, it will be understood that when an element or layer is referred to as being “between” two elements or layers, it can be the only element or layer between the two elements or layers, or one or more intervening elements or layers may also be present.

[0052] Hereinafter, a perovskite light-emitting device according to some embodiments of the present disclosure will be described.

[0053] Figure 1 A cross-sectional view of a perovskite light-emitting device according to an embodiment of the present disclosure is schematically shown.

[0054] refer to Figure 1 According to one embodiment of the present disclosure, a perovskite light-emitting device includes: a first electrode 200 disposed on a substrate 100, a hole transport layer 300 disposed on the first electrode 200, a perovskite light-emitting layer 400 disposed on the transport layer 300, an electron transport layer 500 disposed on the perovskite light-emitting layer 400, and a second electrode 600 disposed on the electron transport layer 500.

[0055] In the perovskite light-emitting device, when a voltage is applied across the first electrode 200 and the second electrode 600, holes injected from the first electrode 200 move to the perovskite light-emitting layer 400 through the hole transport layer 300, and electrons injected from the second electrode 600 move to the perovskite light-emitting layer 400 through the electron transport layer 500. Carriers such as holes and electrons recombine with each other in the perovskite light-emitting layer 400 to generate excitons. When the excitons change from an excited state to a ground state, light is emitted.

[0056] The substrate 100 may be a substrate used in a conventional semiconductor process. For example, the substrate 100 may include silicon, silicon oxide, metal foil (eg, copper foil, aluminum foil, stainless steel foil, etc.), metal oxide, polymer substrate, and combinations thereof.

[0057] The metal foil may be made of a material having a high melting point and not used as a catalyst capable of forming graphene. Examples of metal oxides include aluminum oxide, molybdenum oxide, indium tin oxide, etc. Examples of polymer substrates include Kepton foil, polyethersulfone (PES), polyacrylate (PAR), polyetherimide (PEI), polyethylene naphthalate (PEN), polyethylene terephthalate (PET), polyphenylene sulfide (PPS), polyacrylate, polyimide, polycarbonate (PC), cellulose triacetate (TAC), cellulose acetate propionate (CAP), etc. However, the present disclosure is not limited thereto.

[0058] The first electrode 200 may be made of a conductive polymer, or a conductive metal oxide, such as indium tin oxide (ITO) or fluorine-doped tin oxide (FTO), but is not limited thereto. For example, the first electrode 200 may be made of graphene, carbon nanotubes, reduced graphene oxide, metal nanowires, or metal meshes.

[0059] The first electrode 200 may be formed using a deposition process such as physical vapor deposition (PVD), chemical vapor deposition (CVD), sputtering, pulsed laser deposition (PLD), thermal evaporation, electron beam evaporation, atomic layer deposition (ALD), or molecular beam epitaxy (MBE).

[0060] In one example, the first electrode 200 may have a structure including a conductive layer (not shown) and a surface energy adjustment layer (not shown). Specifically, the surface energy adjustment layer may be disposed on the conductive layer.

[0061] The conductive layer may include a conductive polymer and a first fluorine-based material. The surface energy adjustment layer may include a second fluorine-based material, but may not include the conductive polymer included in the conductive layer. In this regard, the first fluorine-based material and the second fluorine-based material may be the same or different from each other.

[0062] For example, the conductive polymer may include polythiophene, polyaniline, polypyrrole, polystyrene, polyethylenedioxythiophene, polyacetylene, polyphenylene, polyphenylvinylene, polycarbazole, copolymers containing two or more different repeating units thereof, derivatives thereof, or blends of two or more thereof.

[0063] In this regard, the absolute value of the ionization potential energy level of the surface energy adjustment layer is greater than the absolute value of the ionization potential energy level (or HOMO energy: highest occupied molecular orbital energy level) of the perovskite light-emitting layer 400. Therefore, the transfer of holes from the surface energy adjustment layer to the perovskite light-emitting layer 400 can be smoothly performed. Therefore, since the exciton generation efficiency in the perovskite light-emitting layer 400 can be increased, the characteristics of the perovskite light-emitting device, such as efficiency, low driving voltage, and life span, can be improved.

[0064] The hole transport layer 300 disposed on the first electrode 200 may include a material having a hole mobility greater than an electron mobility under the same electric field.

[0065] More specifically, the hole transport layer 300 may include a compound represented by the following Chemical Formula 1 or the following Chemical Formula 2, or include both the compound represented by the following Chemical Formula 1 and the compound represented by Chemical Formula 2:

[0066] [Chemical formula 1]

[0067] -Ar1-Ar2-

[0068] [Chemical formula 2]

[0069]

[0070] In this regard, Ar1 is represented by the following Chemical Formula 3:

[0071] [Chemical formula 3]

[0072]

[0073] wherein each of R1 and R2 is independently selected from -C n H 2n -XY + (n is an integer from 1 to 20) and -Ar3-(OC n H 2n -X - Y + ) l (n is an integer from 1 to 20, l is an integer from 1 to 3), Ar3 is phenyl, pyrrolyl, furyl, thienyl or selenophene, X - SO3 - 、CO2 - or PO3 2- , and Y + Yes H + , Li + 、Na + , K + , Rb + , Cs + NH4 + or NR3R4R5R6 + , each of R3 to R6 is independently selected from an alkyl group having 1 to 20 carbon atoms, Ar2 is a substituted or unsubstituted aryl group, and m is an integer from 2 to 1,000,000.

[0074] In this regard, an alkyl group having 1 to 20 carbon atoms refers to a saturated aliphatic group having 1 to 20 carbon atoms, including a straight chain alkyl group and a branched alkyl group. A straight chain or branched alkyl group may have 10 or less (e.g., C1-C 10 Straight chain, C3-C 10 branched), preferably 4 or less, more preferably 3 or less carbon atoms.

[0075] Specifically, the alkyl group may include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, pentan-1-yl, pentan-2-yl, pentan-3-yl, 3-methylbutan-1-yl, 3-methylbutan-2-yl, 2-methylbutan-2-yl, 2,2,2-trimethylethan-1-yl, n-hexyl, n-heptyl and n-octyl, but is not necessarily limited thereto.

[0076] As used herein, unless otherwise defined, aryl refers to an unsaturated aromatic ring including monocycle or polycyclic (preferably 1-4 ring) fused or covalently attached to each other. The limiting examples of aryl can include phenyl, biphenyl, ortho-terphenyl, meta-terphenyl, para-terphenyl, 1-naphthyl, 2-naphthyl, 1-anthracenyl, 2-anthracenyl, 9-anthracenyl, 1-phenanthrenyl, 2-phenanthrenyl, 3-phenanthrenyl, 4-phenanthrenyl, 9-phenanthrenyl, 1-pyrenyl, 2-pyrenyl and 4-pyrenyl.

[0077] Ar2 may be a substituted or unsubstituted aryl group. When Ar2 is a substituted aryl group, any hydrogen bonded to a carbon in the aryl group may be substituted with a functional group selected from the group consisting of deuterium, substituted or unsubstituted C1-C 10 Alkyl, substituted or unsubstituted C2-C 10 Heteroalkyl, substituted or unsubstituted C2-C 10 Alkenyl, substituted or unsubstituted C2-C 10 Alkynyl, substituted or unsubstituted C2-C 10 Alkoxy, substituted or unsubstituted aryloxy, substituted or unsubstituted C1-C 10 The term "ar2" refers to a group consisting of a halogenated alkyl, a halogen, a cyano group, a hydroxyl group, a substituted or unsubstituted amino group, a substituted or unsubstituted amide, a carbamate, a nitro group, a carboxyl group, a carboxylate, a substituted or unsubstituted aryl group, a substituted or unsubstituted heteroaryl group, a substituted or unsubstituted aralkyl group, and a quaternary ammonium group. However, the type of the functional group replacing the hydrogen in Ar2 can be determined as long as the performance of the hole transport layer material represented by Chemical Formula 1 and / or Chemical Formula 2 as expected herein is not destroyed.

[0078] Ar3 may independently be phenyl, pyrrolyl, furyl, thienyl or selenophenyl having 1 to 3 alkoxy substituents, and may include groups having the following formula:

[0079]

[0080] In this context, M is oxygen, nitrogen, sulfur or selenium.

[0081] In this article, halogen refers to fluorine (-F), chlorine (-Cl), bromine (-Br) or iodine (-I). Haloalkyl refers to an alkyl substituted by the above halogen. For example, halomethyl refers to methyl (-CH2X, -CHX2 or -CX3), wherein at least one hydrogen of the methyl has been replaced by halogen.

[0082] In addition, in this article, alkoxy refers to -O-(alkyl) groups and -O-(unsubstituted cycloalkyl) groups. In this regard, alkyl refers to a straight chain or branched alkyl group having 1 to 10 carbon atoms, and unsubstituted cycloalkyl refers to a cycloalkyl group having 3 to 10 carbon atoms.

[0083] Specifically, the alkoxy group includes methoxy, ethoxy, propoxy, isopropoxy, n-butoxy, tert-butoxy, sec-butoxy, n-pentoxy, n-hexoxy, 1,2-dimethylbutoxy, cyclopropyloxy, cyclobutyloxy, cyclopentyloxy, cyclohexyloxy and the like, but is not limited thereto.

[0084] When the functional group replacing the hydrogen in Ar2 is an alkenyl or alkynyl group, the sp 2 The sp-hybridized carbon of the alkyl group or the sp-hybridized carbon of the alkynyl group may be directly bonded to Ar2 or may be indirectly bonded to Ar2 via the sp3-hybridized carbon of the alkyl group which is bonded to the sp 2 -hybridized carbon or sp-hybridized carbon of an alkynyl group.

[0085] Herein, heteroaryl refers to a functional group in which at least one carbon atom in the aryl group as defined above is replaced by a non-carbon atom such as nitrogen, oxygen or sulfur.

[0086] Non-limiting examples of heteroaryl groups can include furanyl, tetrahydrofuranyl, pyrrolyl, pyrrolidinyl, thiophenyl, tetrahydrothiophenyl, oxazolyl, isoxazolyl, triazolyl, thiazolyl, isothiazolyl, pyrazolyl, pyrazolidinyl, oxadiazolyl, thiadiazolyl, imidazolyl, imidazolinyl, pyridinyl, pyridazinyl, triazinyl, piperidinyl, morpholinyl, thiomorpholinyl, pyrazinyl, piperazinyl, pyrimidinyl, naphthyl, The invention also includes but is not limited to benzofuranyl, benzothiophenyl, indolyl, indolyl, indolizinyl, indazolyl, quinolizinyl, quinolyl, isoquinolyl, cinolinyl, phthalazinyl, quinazolinyl, quinoxalinyl, pteridinyl, quinuclidine, carbazolyl, acridinyl, phenazinyl, phenothiazinyl, phenoxazinyl, purinyl, benzimidazolyl, benzothiazolyl, etc. and their related analogs.

[0087] As used herein, aralkyl refers to a functional group that is an alkyl group substituted with an aryl group and is -(CH2) n A generic term for Ar. Examples of aralkyl groups include benzyl (-CH2C6H5) or phenethyl (-CH2CH2C6H5).

[0088] Herein, unless otherwise defined, a cycloalkyl group or a heterocycloalkyl group containing a heteroatom may be understood as a cyclic structure of an alkyl group or a heteroalkyl group, respectively.

[0089] Non-limiting examples of cycloalkyl include cyclopentyl, cyclohexyl, 1-cyclohexenyl, 3-cyclohexenyl, cycloheptyl and the like.

[0090] Non-limiting examples of cycloalkyl groups containing heteroatoms include 1-(1,2,5,6-tetrahydropyridinyl), 1-piperidinyl, 2-piperidinyl, 3-piperidinyl, 4-morpholinyl, 3-morpholinyl, tetrahydrofuran-2-yl, tetrahydrofuran-3-yl, tetrahydrothiophen-2-yl, tetrahydrothiophen-3-yl, 1-piperazinyl, and 2-piperazinyl, and the like.

[0091] Furthermore, the cycloalkyl group or the cycloalkyl group containing a heteroatom may have a form in which a cycloalkyl group, a cycloalkyl group containing a heteroatom, an aryl group or a heteroaryl group is condensed or covalently linked thereto.

[0092] The compound represented by Chemical Formula 1 and / or Chemical Formula 2 may include the following compounds, and are merely examples of representative compounds, and are not necessarily limited thereto.

[0093]

[0094]

[0095] The compound represented by Chemical Formula 1 and / or Chemical Formula 2 including FPS-K, FPS-TMA, and MPS-TMA has conductivity. Therefore, the layer including the compound represented by Chemical Formula 1 and / or Chemical Formula 2 may be used as a hole transport layer.

[0096] Furthermore, unlike PEDOT:PSS included in a conventional hole transport layer, the compound represented by Chemical Formula 1 and / or Chemical Formula 2 has a neutral pH, thereby preventing degradation of performance, stability, and lifespan of a light-emitting device caused by acidic PEDOT:PSS.

[0097] Conventional passivation materials used to improve the crystallinity of perovskite grown on the hole transport layer 300 are generally non-conductive and thus have limitations in transporting holes. However, the compound represented by Chemical Formula 1 and / or Chemical Formula 2 has an ionic functional group (e.g., K + 、N + (CH3)4), so its ionic properties can be controlled in an easy manner. When the compound contains ions contained in the perovskite light-emitting layer 400, a passivation effect can be imparted to the interface between the hole transport layer 300 and the perovskite light-emitting layer 400. Therefore, when the perovskite light-emitting layer is grown on the hole transport layer 300, defects in the perovskite light-emitting layer 400 can be prevented.

[0098] In particular, MPS-TMA may include a benzene ring not only in the main chain but also in the side chain, thereby improving the hydrophobicity of the compound. In this case, on the surface of the hole transport layer 300 including MPS-TMA, the contact angle of water may be 10° or more, preferably 15° or more, which is greater than the contact angle of water on the surface of PEDOT:PSS, 13.8°. In this way, the hole transport layer 300 including MPS-TMA improves the hydrophobicity of the top surface of the hole transport layer 300 on which the perovskite light-emitting layer 400 is formed. Therefore, when a precursor for forming the perovskite light-emitting layer 400 is coated on the hole transport layer 300, damage to the hole transport layer 300 can be reduced.

[0099] Figure 2 Energy diagrams of perovskite light-emitting devices using PEDOT:PSS and compounds represented by Chemical Formula 1 and / or Chemical Formula 2 (FPS-K, FPS-TMA, MPS-TMA), respectively, are shown.

[0100] refer to Figure 2 , the HOMO energy level of the hole transport layer 300 including the compound represented by Chemical Formula 1 and / or Chemical Formula 2 may be 5.0 to 6.0 eV. The difference between the HOMO energy level of the hole transport layer 300 including the compound represented by Chemical Formula 1 and / or Chemical Formula 2 and the perovskite light emitting layer 400 may be 0.26 eV or less. In addition, the difference between the LUMO energy level of the hole transport layer 300 including the compound represented by Chemical Formula 1 and / or Chemical Formula 2 and the perovskite light emitting layer 400 may be 0.3 eV or more.

[0101] The HOMO level of the hole transport layer containing PEDOT:PSS used as a conventional hole transport material is about 5.01 eV. The difference between the HOMO levels of the hole transport layer containing PEDOT:PSS and the perovskite light emitting layer 400 is about 0.70 eV or more, which can act as a large hole injection barrier. On the other hand, unlike PEDOT:PSS, the compound represented by Chemical Formula 1 and / or Chemical Formula 2 has a "deep" HOMO level, and thus may contribute to the absence of a hole injection barrier.

[0102] In addition, reference Figure 2 , the hole transport layer 300 including the compound represented by Chemical Formula 1 and / or Chemical Formula 2 has a low LUMO energy level of 2.70 to 3.0 eV, so that there is a large gap between its conduction band and the conduction band of the perovskite light-emitting layer 400. Therefore, electrons can be effectively blocked in the hole transport layer 300, thereby improving the recombination efficiency of holes and electrons in the perovskite light-emitting layer 400.

[0103] In addition, the hole transport layer 300 may be post-treated by applying electrical stress thereto.

[0104] In this regard, applying electrical stress may refer to a post-processing in which an electric field is generated between the first electrode 200 and the second electrode 600 to allow ions contained in the compound represented by Chemical Formula 1 and / or Chemical Formula 2 to be effectively passivated on the surface of the hole transport layer 300 on which the perovskite light emitting layer 400 is formed.

[0105] In addition, the post-treatment herein may further include an aging treatment, in which the packaged perovskite light-emitting device after applying electrical stress thereto is kept at room temperature for 24 hours or more.

[0106] Through the aging process, defects at the perovskite crystal interface can be more effectively passivated through ion flow at the interface between the hole transport layer 300 and the perovskite light emitting layer 400 .

[0107] The perovskite light emitting layer 400 may include a metal halide perovskite material.

[0108] In this regard, metal halide perovskite materials have ABX3, A2BX4, ABX4 or A n-1 Pb n I 3n+1 (n is an integer from 2 to 6), wherein A can be a monovalent organic cation or a monovalent metal cation, B can be a divalent or trivalent metal ion, and X can be a monovalent halide ion.

[0109] For example, A can be an amidinium-based organic ion, an organic ammonium cation, or a monovalent alkali metal cation. B can be Pb, Mn, Cu, Ga, Ge, In, Al, Sb, Bi, Po, Sn, Eu, Yb, Ni, Co, Fe, Cr, Pd, Cd, Ca, Sr, or a combination thereof. X can be Cl, Br, I, or a combination thereof.

[0110] The crystal structure of metal halide perovskite materials has a face-centered cubic (FCC) structure, in which the central metal (M) is located at the center and the six halogen elements (X) are respectively arranged at all faces of the hexahedron, or has a body-centered cubic (BCC) structure, in which eight organic ammoniums (RNH3) are respectively located at all vertices of the hexahedron.

[0111] In this regard, the crystal structure of the metal halide perovskite material may have a cubic structure in which all faces of the hexahedron intersect each other at 90°, and the width, length, and height are equal to each other; or a tetragonal structure in which all faces of the hexahedron intersect each other at 90°, and the width and length are equal to each other but different from the height.

[0112] In addition, the metal halide perovskite material of the perovskite light emitting layer 400 may have a perovskite crystal structure including a mixture of an organic material and an inorganic material. The organic and inorganic materials of the metal halide perovskite material may include CH3NH3, and Pb and X (Cl, Br or I), respectively. The present disclosure is not necessarily limited thereto.

[0113] For example, the metal halide perovskite material can be CH3NH3PbBr3, CH3NH3PbBr 3-x I x or CH3NH3PbBr 3- x Cl x .

[0114] The metal halide perovskite material may include A2BX4, ABX4 or A2BX4 having a two-dimensional structure in a layered shape. n- 1Pb n I (n is an integer of 2 to 6). In this regard, A is an organic ammonium material, B is a metal material, and X is a halogen element.

[0115] For example, A can be (CH3NH3) n , (C x H 2x+1 NH3)2(CH3NH3) n 、(RNH3)2、(C n H 2n+1 NH3)2、(CF3NH3)、(CF3NH3) n , (C x F 2x+1 NH3)2(CF3NH3) n or (C n F 2n+1 NH3)2 (n and x are integers greater than 1). B can be a divalent or trivalent transition metal, a rare earth metal, an alkaline earth metal, Pb, Sn, Ge, Ga, In, Al, Sb, Bi, Po or a combination thereof. In this regard, the rare earth metal can be Ge, Sn, Pb, Eu or Yb. The alkaline earth metal can be Ca or Sr. X can be Cl, Br, I or a combination thereof.

[0116] In the perovskite light-emitting device according to one embodiment of the present disclosure, the thickness of the perovskite light-emitting layer 400 may be 500 nm or less, preferably less than 150 nm.

[0117] Generally, when a perovskite is grown on a hole transport layer including PEDOT:PSS as a hole transport material, a perovskite light emitting layer having low crystallinity may be formed or defects may occur in the perovskite light emitting layer due to various reasons as described above. Thus, for example, even when the formed perovskite light emitting layer has a thickness of 150 nm or more, perovskite crystals are formed, but due to many defects at the interface, large leakage current and non-radiative recombination are induced, resulting in reduced efficiency of the light emitting device.

[0118] In one example, according to the present disclosure, the hole transport layer 300 includes a compound represented by Chemical Formula 1 and / or Chemical Formula 2. Compared to PEDOT:PSS, the compound represented by Chemical Formula 1 and / or Chemical Formula 2 can improve the crystallinity of the perovskite light-emitting layer 400 grown on the hole transport layer 300 and can reduce interface defects due to neutral pH characteristics and counter ions.

[0119] In other words, the compound represented by Chemical Formula 1 and / or Chemical Formula 2 passivates defects in the crystal of the perovskite light emitting layer 400 located at the interface of the hole transport layer 300 , so that a more stabilized perovskite phase may be grown.

[0120] Therefore, the perovskite light-emitting device according to one embodiment of the present disclosure can exhibit sufficient light-emitting characteristics even when the employed perovskite light-emitting layer 400 has a smaller thickness (eg, 10 nm) compared to the case of using PEODT:PSS.

[0121] The electron transport layer 500 on the perovskite light-emitting layer 400 may include known electron transport materials such as Alq3 (tris(8-hydroxyquinolinato)aluminum), TAZ (3-(biphenyl-4-yl)-5-(4-tert-butylphenyl)-4-phenyl-4H-1,2,4-triazole), BAlq (bis(8-hydroxy-2-methylquinolinato)-(4-phenylphenoxy)aluminum), BeBq2 (bis(10-hydroxybenzo[h]quinolinato)beryllium), BCP (bathocuproine), Bphen (diphenylphenanthroline (Batho phenanthroline)), TBPI (2,2',2"-(1,3,5-benzenetriyl)-tri(1-phenyl-1-H-benzimidazole)), TmPyPB (1,3,5-tri(m-pyridin-3-ylphenyl)benzene), 3TPYMB (tri(2,4,6-trimethyl-3-(pyridin-3-yl)phenyl)borane) or TpPyPB (1,3,5-tri(p-pyridin-3-yl-phenyl)benzene. In addition, although not shown separately, the electron injection layer can be provided on the electron transport layer 500.

[0122] The second electrode 600 disposed on the electron injection layer can be made of a metal having a relatively low work function, an alloy thereof, a conductive compound, and a combination thereof. Specific examples thereof include lithium (Li), magnesium (Mg), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), and magnesium-silver (Mg-Ag).

[0123] Hereinafter, specific examples of the present disclosure are given. However, the examples described below are only intended to specifically illustrate or describe the present disclosure, and the present disclosure should not be limited thereto.

[0124] Example 1

[0125] After coating ITO as the first electrode on a glass substrate, a solution containing the following compound [FPS-K] (3 mg / ml in a co-solvent (methanol + deionized water)) was spin-coated (5000 rpm, 45 sec) on the first electrode and then heat-treated at 100°C for 10 min to form a 5 nm thick hole transport layer.

[0126]

[0127] Lead bromide (PbBr2), formamidine hydrobromide (FABr) and benzylamine hydrobromide (PMABr) were dissolved in a solvent (DFM:DMSO=7:3) at a concentration of 0.3 M (based on Pb) to prepare PMA2FA2Pb3Br 10 Solution.

[0128] PMA2FA2Pb3Br 10 After the solution was spin-coated on the hole transport layer (3000 rpm, 30 seconds), chlorobenzene as an anti-solvent was dropped thereon to form a 150 nm thick perovskite light-emitting layer.

[0129] Subsequently, a 50 nm thick TPBi electron transport layer, a 1 nm thick LiF electron injection layer and a 100 nm thick second electrode (Al) were thermally deposited in sequence on the perovskite light-emitting layer to prepare a perovskite light-emitting device.

[0130] Example 2

[0131] A perovskite light-emitting device was prepared in the same manner as in Example 1, except that the compound [FPS-TMA] was used instead of the compound [FPS-K].

[0132]

[0133] Example 3

[0134] A perovskite light-emitting device was prepared in the same manner as in Example 1, except that the compound [MPS-TMA] was used instead of the compound [FPS-K].

[0135]

[0136] Comparative Example 1

[0137] A perovskite light-emitting device was prepared in the same manner as in Example 1, except that PEDOT:PSS was used instead of the compound [FPS-K].

[0138] Experimental Example 1. Measurement of HOMO Level of Hole Transport Layer

[0139] Using ultraviolet electron spectroscopy (UPS), the HOMO level of the hole transport layer of the perovskite light-emitting device prepared according to each of Examples 1 to 3 and Comparative Example 1 was measured. The measurement results are shown in Figures 3 to 6 ,

[0140] refer to Figures 3 to 6 , the HOMO energy level of PEDOT:PSS is 5.01 eV, the HOMO energy level of FPS-K is 5.98 eV, the HOMO energy level of FPS-TMA is 5.80 eV, and the HOMO energy level of MPS-TMA is 5.70 eV.

[0141] refer to Figure 2 , which shows an energy diagram of a perovskite light-emitting device, it can be determined that the HOMO energy level of the hole transport layer containing the compound represented by Chemical Formula 1 or Chemical Formula 2 is 5.60 to 6.0 eV, and the difference in HOMO energy levels between the hole transport layer containing the compound represented by Chemical Formula 1 or Chemical Formula 2 and the perovskite light-emitting layer is 0.26 eV or less.

[0142] On the other hand, it can be confirmed that the HOMO energy level of the hole transport layer containing PEDOT:PSS is about 5.01eV, and the difference in HOMO energy level between the perovskite light emitting layer and the hole transport layer containing PEDOT:PSS is about 0.70eV or more. Therefore, unlike the hole transport layer containing the compound represented by Chemical Formula 1 or Chemical Formula 2, a large hole injection barrier occurs in Comparative Example 1.

[0143] Experimental Example 2. Measurement of the contact angle of water on the surface of the hole transport layer

[0144] When the hole transport layer has high hydrophilicity, this can improve the crystallinity of the perovskite grown on the hole transport layer due to its good compatibility with the perovskite. However, when the perovskite precursor material is coated on the hole transport layer, the possibility of damage to the surface of the hole transport layer due to the perovskite precursor material may also increase.

[0145] In order to measure the hydrophilicity of the hole transport layer of the perovskite light-emitting device prepared according to each of Examples 1 to 3 and Comparative Example 1, after forming the hole transport layer, water (H2O) was dropped on the surface thereof to measure the surface contact angle. The measurement results are shown in Figures 7 to 10 .

[0146] refer to Figures 7 to 10 , the hole transport layer including each of FPS-K and FPS-TMA and PEDOT:PSS exhibited a contact angle of water on the surface of about 15° or less, showing a hydrophilic surface. However, when MPS-TMA was included in the hole transport layer, its hydrophobicity was relatively increased compared to other hole transport layers.

[0147] As described above, the hole transport layer including MPS-TMA exhibits a hydrophobic surface. Therefore, during the spin coating of the perovskite precursor material, even when a portion of the hole transport layer is dissolved, aggregation between the hole transport materials can be suppressed, thereby preventing damage to the hole transport layer.

[0148] Experimental Example 3. Measurement of PL lifetime of perovskite light-emitting device

[0149] Excitation light was irradiated to the perovskite light-emitting device prepared according to each of Examples 1 to 3 and Comparative Example 1. Then, the PL lifetime thereof was measured based on the irradiation duration of the excitation light.

[0150] Fig.11 Table 1 and Table 1 show the measurement results of the PL lifetimes of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1, respectively.

[0151] Table 1

[0152] Example <![CDATA[τ 平均 (ns)]]> χ2 Example 1 5.42 1.2516 Example 2 9.99 1.1731 Example 3 10.47 1.2315 Comparative Example 1 1.70 1.1150 Example 1 (Aging) 5.79 1.1792 Example 2 (Aging) 17.53 1.1801 Example 3 (Aging) 19.96 1.1557 Comparative Example 1 (Aging) 0.62 1.1564

[0153] Referring to the PL lifetime measurement results, it can be determined that the PL lifetime of the perovskite light-emitting device prepared according to each of Examples 1 to 3 is longer than the PL lifetime of the perovskite light-emitting device prepared according to Comparative Example 1. This is because, in the perovskite light-emitting device prepared according to Comparative Example 1, defects in the perovskite light-emitting layer are caused by PEDOT:PSS in the hole transport layer, and thus PL quenching occurs, thereby reducing the PL lifetime.

[0154] In the perovskite light-emitting device prepared according to each of Examples 2 and 3, the counter ions of the hole transport material include ions contained in the perovskite light-emitting layer. Therefore, a passivation effect on the perovskite crystal defects located at the interface between the hole transport layer and the perovskite light-emitting layer can be achieved. Therefore, it can be determined that the PL lifetime of the perovskite light-emitting device prepared according to each of Examples 2 and 3 is relatively longer than the PL lifetime of the perovskite light-emitting device prepared in Example 1.

[0155] Furthermore, in Example 3, it can be confirmed that, compared with the PL lifetimes of Examples 1 and 2, the hole transport layer is less damaged due to the hydrophobicity of MPS-TMA, and thus the PL lifetime is relatively longer.

[0156] In one embodiment, after preparing a perovskite light-emitting device according to each of Examples 1 to 3 and Comparative Example 1 and then encapsulating the device, the encapsulated device is aged for 24 hours at room temperature and in a nitrogen atmosphere, and then its PL lifetime is measured under the same conditions. Therefore, it can be seen that the perovskite light-emitting device prepared according to Comparative Example 1 has a short PL lifetime, while the perovskite light-emitting device prepared according to Examples 1 to 3 has a longer PL lifetime.

[0157] Experimental Example 4. Performance evaluation of perovskite light-emitting device

[0158] The current density, luminance, luminous efficiency, power efficiency, and external quantum efficiency (EQE) of each of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 were measured.

[0159] Fig.12 The measurement results of the current density of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown.

[0160] refer to Fig.12 , it can be determined that there is leakage current in the low voltage region (0 to 2 V) in Comparative Example 1. This measurement result can be determined to be caused by defects in the perovskite light emitting layer caused by using a hole transport layer containing PEDOT:PSS.

[0161] Fig.13 The measurement results of the luminance of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown. Fig.14 The measurement results of the luminous efficiency of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown. Fig.15 The measurement results of the external quantum efficiency of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 are shown. Fig.16The results of the measurement of the change in external quantum efficiency of the perovskite light-emitting devices prepared according to Examples 1 to 3 and Comparative Example 1 before and after aging treatment for 24 hours in a nitrogen atmosphere at room temperature are shown. In addition, Table 2 describes Figures 13 to 16 The measurement results.

[0162] Table 2

[0163]

[0164] refer to Figures 13 to 16 From the results in Table 2, it can be determined that the performance of the perovskite light-emitting device prepared according to each of Examples 1 to 3 is improved compared to Comparative Example 1. It can be determined that among these examples, the perovskite light-emitting device prepared according to Example 3 has the highest performance. It can be expected that the difference in performance of the perovskite light-emitting device is caused by the same reason as the reason that causes the difference in PL lifetime of the perovskite light-emitting device in Experimental Example 3.

[0165] In addition, the perovskite light-emitting device prepared according to Comparative Example 1 showed a decrease in overall light-emitting device performance after aging, while the perovskite light-emitting device prepared according to each of Examples 1 to 3 showed an improvement in overall light-emitting device performance after aging.

[0166] Experimental Example 5. Interface evaluation of perovskite light-emitting device

[0167] Using XPS (X-ray photoelectron spectroscopy) and XRD (X-ray diffraction) analysis, the interface between the hole transport layer and the perovskite light-emitting layer of the perovskite light-emitting device prepared according to each of Example 1, Example 2 and Comparative Example 1, that is, the perovskite crystallinity on the surface of the perovskite light-emitting layer in contact with the hole transport layer was evaluated.

[0168] Fig.17 The XPS analysis results of the perovskite light-emitting devices prepared according to Example 1, Example 2 and Comparative Example 1 are shown. Fig.18 The XRD analysis results of the perovskite light-emitting devices prepared according to Example 1, Example 2 and Comparative Example 1 are shown.

[0169] refer to Fig.17 , when a 10 nm thick perovskite light emitting layer is grown, the perovskite light emitting device according to Comparative Example 1 has the highest binding energy of Pb 4f. Example 1 and Example 2 have the next lower binding energy in turn. This means that compared with PEDOT:PSS, the compound represented by Chemical Formula 1 and / or Chemical Formula 2 can form a perovskite light emitting layer with less PbBr2 and less halide vacancy defects.

[0170] refer to Fig.18, when a 10 nm thick perovskite light-emitting layer was grown on the hole transport layer, the XRD peak of perovskite could be determined in the perovskite light-emitting devices prepared according to each of Examples 1 and 2. However, the XRD peak of perovskite could not be determined in the perovskite light-emitting device prepared according to Comparative Example 1.

[0171] In one example, if Fig.19 and Fig. 20 As shown in , when the thickness of the perovskite light-emitting layer is 150 nm, the XRD peaks of the perovskite crystals can be determined in all the perovskite light-emitting devices prepared according to Example 1, Example 2 and Comparative Example 1, unlike the case where the thickness of the perovskite light-emitting layer is 10 nm.

[0172] That is, as the thickness of the perovskite light-emitting layer increases, the influence of defects caused by the hole transport material contained in the hole transport layer tends to decrease. However, even when the perovskite light-emitting layer is formed to have a thickness of 150 nm or more, perovskite crystals are formed, but many defects at the interface still cause a large amount of leakage current and non-radiative recombination, thereby reducing the efficiency of the perovskite light-emitting device.

[0173] Experimental Example 6. Evaluation of performance changes of perovskite light-emitting devices based on application of electrical stress

[0174] In order to evaluate the performance change of the perovskite light-emitting device according to the application of electrical stress, while increasing the current density applied to the perovskite light-emitting device prepared according to each of Example 1, Example 2 and Comparative Example 1, the change in external quantum efficiency (EQE) was measured.

[0175] Fig.21 The results are shown based on the electrical stress (current density 0.5 mA / cm2) applied to the perovskite light-emitting device prepared according to each of Example 1, Example 2 and Comparative Example 1 in the driving direction of the light-emitting device. 2 , electrical stress application time: 30 seconds) are the measurement results of the change in external quantum efficiency.

[0176] Fig. 22 The results show that electrical stress (current density 0.5 mA / cm2) was applied to the perovskite light-emitting device prepared according to each of Example 1, Example 2 and Comparative Example 1 in the driving direction of the light-emitting device. 2 , electrical stress application time: 30 seconds) before / after the measurement results of the change in external quantum efficiency.

[0177] refer to Fig.21 and Fig. 22It can be seen that it can be determined that in the perovskite light-emitting device prepared according to Comparative Example 1, after applying electrical stress, the external quantum efficiency decreases, while in the perovskite light-emitting device prepared according to each of Examples 1 and 2, after applying electrical stress, the external quantum efficiency of the light-emitting device increases.

[0178] The above description is based on the embodiments shown in the drawings, but various changes or modifications may be made thereto at the level of those skilled in the art. Therefore, as long as these changes and modifications do not depart from the scope of the present disclosure, they may be understood to be included in the scope of the present disclosure.

Claims

1. A perovskite light-emitting device, comprising: a first electrode; a hole transport layer disposed on the first electrode; A perovskite light-emitting layer disposed on the hole transport layer; An electron transport layer disposed on the perovskite light-emitting layer; and A second electrode disposed on the electron transport layer, The hole transport layer comprises a compound represented by the following Chemical Formula 1 or the following Chemical Formula 2: [Chemical formula 1] --Ar1-Ar2-- [Chemical formula 2] Wherein Ar1 is represented by the following chemical formula 3: [Chemical formula 3] wherein each of R1 and R2 is independently selected from -C n H 2n -X - Y + , wherein n is an integer from 1 to 10; and -Ar3-(OC n H 2n -X - Y + ) l , wherein n is an integer from 1 to 10, l is an integer from 1 to 3, wherein Ar3 is phenylene, Where X - SO3 - , and Y + It's Li + 、Na + , K + , Rb + , Cs + NH4 + or NR3R4R5R6 + , wherein each of R3 to R6 is independently selected from an alkyl group having 1 to 4 carbon atoms, wherein Ar2 is phenylene, and wherein m is an integer from 2 to 1,000,000. 2 . The device of claim 1 , wherein the HOMO level of the hole transport layer is in the range of 5.0 to 6.0 eV. 3 . The device according to claim 1 , wherein the difference between the LUMO energy level of the hole transport layer and the LUMO energy level of the perovskite light emitting layer is 0.3 eV or more. 4 . The device according to claim 1 , wherein a contact angle of water on the surface of the hole transport layer is 10° or more.

5. The device of claim 1, wherein the thickness of the perovskite light emitting layer is 500 nm or less.

6. The device of claim 1, wherein the hole transport layer is post-treated using an electrical stress applied in a driving direction of the perovskite light-emitting device.

7. The device of claim 1, wherein the perovskite light-emitting device is encapsulated and then aged at room temperature in a nitrogen atmosphere for at least 12 hours. 8 . The device of claim 2 , wherein the HOMO level of the hole transport layer is in the range of 5.60 to 6.0 eV.

Citation Information

Patent Citations

  • Perovskite type electroluminescence device and preparation method thereof

    CN104681731A

  • P-doped conjugated polymer electrolyte and an organic electronic device using the same

    US20130068305A1